Non-lethal assessment of the reproductive status of broadnose sevengill sharks (Notorynchus cepedianus) to determine the significance of habitat use in coastal areas - Awruch, Cynthia A. (Conserv Physiol, 2014)
Identification of the importance of habitats that are frequently used by any species is essential to a complete understanding of the species' biology and to incorporate their ecological role into conservation and management programmes. In this context, the present study investigated whether Tasmanian coastal waters have any reproductive relevance for the broadnose sevengill shark (Notorynchus cepedianus). Although this species is a large coast-associated apex predator in these areas, there is a complete gap in understanding the role that these coastal systems could play in its reproduction. Reproductive hormones were used as a non-lethal method to address the reproductive biology of this species. Females seemed to have at least a bi-annual reproductive cycle, being pregnant for ∼1 year and spending at least 1 year non-pregnant, with the ovulatory cycle separated from gestation. Mature females were found to be ovulating, in the initial stages of pregnancy, resting or starting a new vitellogenic cycle. Notorynchus cepedianus did not use these coastal habitats for mating or as a pupping ground. Although the mating season was distinguished between September to April, only 22% of males showed mating scars during the peak of the mating period and no near-term pregnant females were observed. Thus, despite these coastal waters being an important foraging ground for this species, these areas did not have any reproductive relevance. In consequence, future management and conservation planning programmes need to identify whether there are other areas in Tasmania that play a critical role for reproductive purposes in this species. Finally, although previous studies have linked reproductive hormones with external examination of the gonads to validate the use of steroids as a non-lethal tool to address reproduction, the present study used this methodology without killing any animals. This has important implications for conservation programmes of threatened and endangered species worldwide where the methodology cannot be validated.